IQOS point-of-sale marketing strategies in Israel: a pilot study - Yael Bar-Zeev; Hagai Levine; Gil Rubinstein; Ihab Khateb; Carla J. Berg (BMC, 2019)
Abstract Background Philip Morris International's IQOS ("I Quit Ordinary Smoking") device has increasingly penetrated the global tobacco market. In Israel, among the first countries with IQOS in its market, the IQOS device is sold in specialty stores and online; the heat sticks - HEETS - are sold at traditional retailers. Advertising restrictions in many contexts including Israel have shifted industry marketing efforts to point-of-sale (POS). Given the nuances of IQOS and HEETS product distribution and the importance of POS marketing, we conducted a pilot study of IQOS POS marketing strategies. Methods Data collectors assessed product offerings, pricing, promotional strategies, and placement in a sample of 15 IQOS retailers (10 convenience stores, 3 grocery stores, 2 tobacco shops) in three Israeli cities (Beer-Sheva, Haifa, Jerusalem). Results All retailers sold cigarettes; many carried other forms of tobacco (e.g., cigar products). Average price for a HEETS package was 30.2 Shekels (SD = 2.7); average price for the least expensive cigarette pack was 27.4 (SD = 1.5). HEETS were on average 9.5% more expensive than cigarettes. Posted ads were uncommon; rather, product displays were prominent. HEETS packages were often placed in a separate display box, at higher and more noticeable positions, and closer to consumers. Additionally, 11 retailers placed cigarettes and 10 placed HEETS near youth-oriented merchandise; 9 retailers placed cigarettes and HEETS, respectively, within 1 m of the floor. Conclusions This study represents an initial step in assessing IQOS POS practices - critical in advancing the ability to facilitate related research and regulation of emerging tobacco products in Israel and more broadly.